2008
DOI: 10.1113/jphysiol.2007.141333
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation of a key cardiac potassium channel can contribute to atrial fibrillation: evidence from an IKs transgenic mouse

Abstract: Inherited gain-of-function mutations of genes coding for subunits of the heart slow potassium (I Ks ) channel can cause familial atrial fibrillation (AF). Here we consider a potentially more prevalent mechanism and hypothesize that β-adrenergic receptor (β-AR)-mediated regulation of the I Ks channel, a natural gain-of-function pathway, can also lead to AF. Using a transgenic I Ks channel mouse model, we studied the role of the channel and its regulation by β-AR stimulation on atrial arrhythmias. In vivo admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…In guard cells, PLC and PLD appear to operate in the same ABA-signaling cascade (45), and phosphatidic acid (PA), the product of PLD activity, is another attractive candidate regulator: PA inhibits guard-cell K in currents (45), and PLD is ABA-activated (45) and regulated by G␣ in guard cells (46). In addition, one class of Shaker-like channels, the KCNQ channels, whose mutation is associated with genetic diseases including long QT syndrome and atrial arrhythmias (47), displays modulation via a G s -dependent cascade, including activation by PtdInsP 2 (47,48). On a sequence homology basis, the guard cell K in channels, despite evincing inward rectification, are similar to metazoan Shaker K ϩ channels (27).…”
Section: Regulation Of Plant Kin Channels By G Protein Complex Componmentioning
confidence: 99%
“…In guard cells, PLC and PLD appear to operate in the same ABA-signaling cascade (45), and phosphatidic acid (PA), the product of PLD activity, is another attractive candidate regulator: PA inhibits guard-cell K in currents (45), and PLD is ABA-activated (45) and regulated by G␣ in guard cells (46). In addition, one class of Shaker-like channels, the KCNQ channels, whose mutation is associated with genetic diseases including long QT syndrome and atrial arrhythmias (47), displays modulation via a G s -dependent cascade, including activation by PtdInsP 2 (47,48). On a sequence homology basis, the guard cell K in channels, despite evincing inward rectification, are similar to metazoan Shaker K ϩ channels (27).…”
Section: Regulation Of Plant Kin Channels By G Protein Complex Componmentioning
confidence: 99%
“…PDE4D3 was found in macromolecular signaling complexes regulating 2 major players of excitation-contraction coupling in rodent heart: the slow delayed rectifier K ϩ current (16) and the ryanodine receptor RyR2 (17). Interestingly, inhibition of PDE4D leads to an increased PKA activation of the slow delayed rectifier K ϩ current (16), which can contribute to AF (18). Here we found that PDE4D was the dominant member of the PDE4 family expressed in human atrium.…”
Section: Discussionmentioning
confidence: 85%
“…Common to some of these mutations in I Ks subunits is a gain-of-function phenotype based mainly on alteration of channel gating and altered functional -subunit modulation upon heterologous expression experiments. Although, care has to be taken to interpret effects on KCNQ1/KCNE channel features in heterologous expression [26], the gainof-function phenotypes may allow for the development of AF as a result of increased I Ks and resultant action potential shortening [27,28]. Very recently, a combined phenotype of LQTS and atrial fibrillation was reported for carriers of the mutation R231C [29].…”
Section: Introductionmentioning
confidence: 99%